2010
DOI: 10.1088/0004-637x/716/1/766
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Abundance in Solar-Type Stars With Low Chromospheric Activity: Application to the Search for Maunder Minimum Analogs

Abstract: We use measurements of lithium abundance to examine the evolutionary history of stars frequently believed to be in a Maunder minimum (MM) state due to their low chromospheric activity. In a sample whose main-sequence membership has been verified using Hipparcos parallax data, we find that stars with very low chromospheric activity log R HK −5.0 have substantially depleted lithium compared with the full sample, with half of these lithium abundances lying more than one standard deviation below the sample mean fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 88 publications
(127 reference statements)
0
14
0
Order By: Relevance
“…As they discussed, however, their values may be overestimated for T eff 5800 K. The difficulties encountered when trying to constrain this parameter from the spectroscopic material routinely secured for abundance studies is illustrated by the fact that Fuhrmann (2004) estimated v sin i = 1.0 km s −1 only for HD 42618 by also adopting a calibrated macroturbulent velocity (ζ RT = 3.3 km s −1 in that particular case). A low-rotation rate is consistent with their low-activity levels (Hall et al 2009;Gray et al 2003;Isaacson & Fischer 2010;Lubin et al 2010). HD 43587 shows no evidence for activity cycles (Baliunas et al 1995) and has even been proposed to go through a Maunder-like minimum (Schröder et al 2012).…”
Section: Methods Of Analysismentioning
confidence: 58%
“…As they discussed, however, their values may be overestimated for T eff 5800 K. The difficulties encountered when trying to constrain this parameter from the spectroscopic material routinely secured for abundance studies is illustrated by the fact that Fuhrmann (2004) estimated v sin i = 1.0 km s −1 only for HD 42618 by also adopting a calibrated macroturbulent velocity (ζ RT = 3.3 km s −1 in that particular case). A low-rotation rate is consistent with their low-activity levels (Hall et al 2009;Gray et al 2003;Isaacson & Fischer 2010;Lubin et al 2010). HD 43587 shows no evidence for activity cycles (Baliunas et al 1995) and has even been proposed to go through a Maunder-like minimum (Schröder et al 2012).…”
Section: Methods Of Analysismentioning
confidence: 58%
“…The comparison was made for the precise determinations of the Li content, but not for the estimations of the upper limits of the Li abundance. As marked in the study by Lubin et al (2010), which collected the determinations of the Li abundance, made in thirty studies by different authors and for various objects, for log A(Li) > 1.5 there is a relatively small dispersion in the Li abundance detections among various measurement programmes, while the scattering increases for lower log A(Li). The difference in log A(Li) is about 0.5-1 dex.…”
Section: Determination Of the LI Abundancementioning
confidence: 99%
“…Wright (2004) suggested that the majority of ''Maunder minimum'' identifications were actually of more evolved stars, and ''there is no unambiguous identification of another star in a Maunder minimum state''. At the very least, such states appear to be rare (see also Lubin et al 2010Lubin et al , 2012), so we must identify and observe a large number of solar analogs in order to unambiguously detect any.…”
Section: Introductionmentioning
confidence: 99%